Effects of standardized ileal digestible tryptophan:lysine ratio on growth performance and economics of finishing pigs - Marcio Antonio Dornelles Goncalves; Michael D Tokach; Steven S Dritz; K J Touchette; Nora M Bello; Joel M DeRouchey; Jason C Woodworth; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2014)
The high usage of dried distillers grains with solubles (DDGS) in swine diets and the economical availability of feed-grade tryptophan have allowed swine nutritionists to include L-tryptophan in practical diet formulations. The objective of these experiments was to determine the effects of different standardized ileal digestible tryptophan:lysine (SID Trp:Lys) ratios on growth performance and economics in finishing pigs. Three 21-d growth experiments with a total of 1,166, 1,099, and 1,132 gilts (337 × 1050; PIC, Hendersonville, TN) and initial BW of 66.0 ± 1.8, 122.2 ± 4.3, and 156.9 ± 2.8 lb were used in Experiments 1, 2, and 3, respectively. At the beginning of each experiment, pigs were weighed in pens, and pens were ranked by average BW and randomly assigned dietary treatments in a randomized complete block design based on BW. Each experiment had 6 pens per treatment with 23 to 28 pigs per pen. Dietary treatments contained 30% DDGS and were 14.5, 16.5, 18.0, 19.5, 21.0, 22.5, and 24.5% SID Trp:Lys ratio. The SID Trp:Lys ratio was increased by adding crystalline L-Trp to the control diet at the expense of corn. Diets were formulated to ensure that lysine was the second limiting amino acid throughout the experiment. From 66.0 to 100.6 lb, ADG increased up to 19.5% SID Trp:Lys ratio then had marginal changes at higher ratios (quadratic, P<0.02), whereas F/G improved through 21.0% SID Trp:Lys ratio then also had marginal changes at higher ratios (quadratic, P<0.004). Income over feed cost (IOFC) increased quadratically (P<0.02) up to 24.5% SID Trp:Lys ratio. From 122.2 to 165.2 lb, pigs fed increasing SID Trp:Lys ratio had increased ADG (linear, P<0.03); however, the higher magnitude of improvement in ADG was through the 18% SID Trp:Lys ratio, with a subtle increase up to the highest SID Trp:Lys ratio. Feed efficiency and IOFC were not statistically different between treatments. From 156.9 to 200.8 lb, ADG, F/G, and IOFC improved (quadratic, P<0.04) through 21.0% SID Trp:Lys ratio, then was poorer for pigs fed the 2 highest SID Trp:Lys ratios. In conclusion, these studies provide good evidence to formulate diets for finishing pigs with at least 18.0% SID Trp:Lys ratio because the growth and economic risk of formulating diets below that ratio is considerably greater than formulating diets above that ratio.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Amino acid ratio; Tryptophan; Finishing pig